TOXICITY TEST OF THE COMBINATION Eleutherine americana Merr. AND Areca vestiaria EXTRACTS AGAINST THE INTESTINAL ORGANS OF Rattus norvegicus - Sarai Raehilda Febriansi Korban; Herny Simbala; Meilani Jayanti (PHARMACON, 2023)
Dayak onions (Eleutherine americanaÂ Merr.) and Pinang Yaki (Areca vestiaria) have been used by the community as traditional medicine. The purpose of this study was to determine the safety level of extracts of Dayak onion and Pinang Yaki against the macroscopic appearance of the intestinal organs of Wistar male white rats. This study used an experimental method with 18 male white rats of the Wistar strain who were given ethanol extract of Dayak onion and Pinang Yaki orally at a dose of 10,8mg, 14,4mg, and 21,6mg for 14 days. The results showed that there was a decrease in body weight, in each treatment group but the largest weight loss occurred in the dose group V from 199gram to 182gram while the smallest weight loss occurred in the dose group I from 199gram to 198gram and for the macroscopic picture of the intestinal organs there was no significant difference between the test group with the control group. In conclusion, the administration of extracts of Dayak onion and Pinang Yaki does not affect the macroscopic picture of the intestinal organs.